Implementasi Pembelajaran Berbasis Steam Melalui Kegiatan Membuat Perahu Nelayan Pada Anak Usia 5-6 Di TK Fii Mardhotillah - Shofia Zahra Rizqia; Dindin Abdul Muiz Lidinillah; Qonita Qonita (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning for early childhood can provide meaningful learning experiences through exploration, experimentation, and problem-solving activities. However, research examining the implementation of STEAM through integrated project-based activities and the emergence of various children's abilities during the learning process is still limited. This study aims to describe the implementation of STEAM learning through the activity of making a fishing boat and examine the various abilities that emerge during the learning process. This study used a qualitative method. The research participants consisted of 11 children aged 5–6 years from Group B1 of Fii Mardhotillah Kindergarten, while the interview informants were class teachers. Data were collected through observation, interviews, and documentation studies. Data analysis used the Miles & Huberman model which includes data reduction, data presentation, and drawing conclusions. The results showed that all elements of STEAM were implemented in an integrated manner in the learning activities. During the learning process, children demonstrated basic science process skills. In addition, the boat-making activity also fostered problem-solving skills through the process of testing and improving designs, developing creativity in product design, and active involvement of children during the learning process. This study concludes that STEAM learning through fishing boat-building activities provides meaningful, contextual, and integrated learning experiences that support the development of various early childhood abilities. The findings are expected to serve as a reference for early childhood education teachers in designing more innovative and meaningful project-based STEAM learning